Climatic cataclysm : the foreign policy and national security implications of climate change - Campbell, Kurt M., 1957- (Brookings Institution Press, 2008)
"Presents three scenarios of what the future may hold: expected, severe, and catastrophic and analyzes the security implications of each. Considers what can be learned from early civilizations confronted with natural disaster and asks what the largest emitters of greenhouse gases can do to reduce and manage future risks"--Provided by publisher